The future of the standard employment relationship: Labour law, new institutional economics and old power resource theory. (June 2017) - Fudge, Judy
This article addresses two questions about the standard employment relationship that have become prominent in labour law literature: Does it exacerbate inequality? Is its decline inevitable? The focus is on the second question and emphasizes the extent to which the standard employment relationship was both embedded in, and the outcome of, an institutional ensemble that was fashioned out of the post-war capital–labour compromise in industrialized democracies. The analysis proceeds in three steps. The first is conceptual and stresses the distinctive nature of labour as a fictive commodity, and the recurring regulatory dilemmas that arise in any attempt to institutionalize a labour market. The second step historicizes and contextualizes the employment relationship, emphasizing politics and conflict (power resource theory) over rational choice and coordination (new institutional economics) as the basis for its institutionalization. The emphasis on politics, power and labour leads to the third step, which focuses on how the broad process of financialization influences three key institutions – the large manufacturing firm, the democratic welfare state and autonomous trade unions – that have been crucial for the development of the standard employment relationship.